Investigation of cell assemblies prepared out of electrocatalysts aimed for hydrogen evolution - Perica Paunović, Orce Popovski, Ivan Radev (Society of Chemists and Technologists of Macedonia, 2005)
Electrode materials, electrodes and finally cell assemblies aimed for hydrogen evolution were prepared, characterized or tested for their performance. Instead of Pt-group metals, non-precious metals as Co and Ni were used to prepare complex hypo-hyper d-electrocatalysts grafted on TiO2 + Carbon. Catalyst composition was 10% Me + 18% TiO2 + Carbon. BET, XRD and SEM were used to determine structural and surface characteristics of the catalysts. Polarization characteristics for hydrogen evolution reaction (HER) of the basic catalyst’s series were further improved by changing the crystallinity and/or the morphology of their components. As a result, overpotentials of hydrogen evolution on these electrocatalysts approach corresponding ones exhibited on Pt-based electrode materials. The catalysts deposited on support containing anatase titania grafted on multi-walled carbon nanotubes (MWCNTs) have shown the best performance. Testing was done in aqueous alkaline cells as gas-diffusion electrodes (GDE) for hydrogen evolution. Nafion PTFA membranes were used to prepare membrane electrode assembly (MEA) with above electrocatalysts. It was shown that the use of a proton exchange membrane (PEM) in the electrochemical cell for hydrogen evolution has a number of advantages. Unusual shape of MEA’s polarization curves was registered. Curves did steepened their slope after reaching given overpotential (–590 mV for Ni based catalyst, –450 mV for CoNi and –420 mV for Co ones). Such a behavior is in contrast to the Pt based catalysts whose slope remains practically constant over the whole region of tested overpotentials. It is important to stress that at higher overpotentials the latter’s activity is very close to that of non-precious metal catalysts, especially Co containing ones. Increasing of temperature contributes to considerable rise of catalytic activity.